Nebenwirkungen von Psychopharmaka: Tipps für die Praxis - Grunze, Anna; Mago, Rajnish; Grunze, Heinz (DMW - Deutsche Medizinische Wochenschrift, 2017)
Psychotropics are highly effective medications that, however, have adverse drug reactions attached to them. They are indispensable for many patients. How to cope with side effects – watchful waiting, dose reduction, change of medication, addition of an “antidote” and behavioural modifications – depends on their nature, severity and finally the patients wish. This review is meant to aid clinician’s and patient’s decisions in case of the occurrence of compromising, frequent adverse drug reactions.
Keywords: Antidepressiva; Antipsychotika; Psychopharmaka; unerwünschte Arzneimittelwirkung/-reaktion